PREFERENCES IN MINI-IMPLANT DIMENSIONS AMONG ROMANIAN ORTHODONTISTS - Teodora Consuela Bungau; Ligia Vaida; Abel Moca; Camelia Liana Buhas; Cristina Ioana Talpoș-Niculescu; Mariana Pacurar; Dragos Craciun; Malina Popa (Romanian Journal of Oral Rehabilitation)
"Introduction. Anchorage in orthodontics is critical for managing malocclusions, traditionally achieved via intraoral appliances. Temporary Anchorage Devices (TADs) like mini-implants offer enhanced control by being temporarily fixed in bone. These devices, made from materials like titanium and stainless steel, vary in size and are selected based on multiple factors, including patient characteristics and anatomical considerations. This study explores the preferences of Romanian orthodontists concerning mini-implant dimensions and systems, addressing a gap in local data and aiming to align practices with evidence-based standards. Materials and methods. This study employed a questionnaire distributed via social media to Romanian dental professionals from June to September 2024. Data on mini-implant usage, preferences for dimensions, and complications were collected. Ethical approval was secured from the Faculty of Medicine and Pharmacy at the University of Oradea, with participant consent implied through questionnaire completion. Statistical analysis was performed using IBM SPSS, focusing on the correlation between mini-implant dimensions and clinical outcomes. Results. Mini-implants are widely used with preferences for specific dimensions varying by anatomical location. The most common sizes in the maxillary interradicular area were 1.6 x 8 mm and 1.6 x 10 mm. Complications were associated with the use of inappropriate mini-implant sizes, particularly in areas requiring precise dimensional fitting. The study found a notable preference for larger and longer mini-implants in regions like the infrazygomatic area, with a significant portion of orthodontists not using mini-implants in less common locations due to variability in training and resource access. Conclusions. Proper selection of mini-implant sizes is crucial for optimizing clinical outcomes and minimizing complications. The study underscores the importance of comprehensive training and access to diverse mini-implant systems to accommodate varied clinical needs and preferences. Future initiatives should focus on standardizing orthodontic practices in Romania to enhance the success rates of orthodontic treatments involving TADs."